Sense Of Multikulturalisme: Potensi Integrasi Dalam Kelompok Teater Pelajar SMA Di Kota Solo - Ansari, Isa; Dipoyono, Achmad (Acintya, 2019)
In general, this study departs from a large scheme of research on Sense of Multiculturalism initiated by the Center for Theater Studies and Social Integration. This is a basic research to explore the potencies that exists among adolescents, both related to the conflict as well as efforts to integrate in high school theater groups. Problems of this research include; first, what potencies that can lead them into conflict areas? What potencies that develops in youth theater groups that can anticipate and strengthen the social integration? Data collection is done by interview, observation, and documentation. The results of this study indicate that the potencies that directs group members into conflict is due to the impartiality experienced by students participating in theater extracurricular activities, both from the school as well as from their family. But their potencies in integration is strongerthan the potencies in conflict, namely independence, maturity, togetherness, cooperation, and kinship among members of the student theater group. Keywords: integration, conflict, students theater